2022
DOI: 10.1038/s41467-022-33428-0
|View full text |Cite
|
Sign up to set email alerts
|

XPF activates break-induced telomere synthesis

Abstract: Alternative Lengthening of Telomeres (ALT) utilizes a recombination mechanism and break-induced DNA synthesis to maintain telomere length without telomerase, but it is unclear how cells initiate ALT. TERRA, telomeric repeat-containing RNA, forms RNA:DNA hybrids (R-loops) at ALT telomeres. We show that depleting TERRA using an RNA-targeting Cas9 system reduces ALT-associated PML bodies, telomere clustering, and telomere lengthening. TERRA interactome reveals that TERRA interacts with an extensive subset of DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…We also analyzed three additional nucleotide excision repair genes, RAD10 , RAD14 and RAD17 , and found that none of them greatly affects type II telomere recombination ( Supplementary Figure S1p–r ). Thus, although mammalian nucleotide excision repair nucleases XPF and XPG have been reported to be involved in processing R-loop structures ( 16 , 17 , 36 ), the yeast nucleotide excision repair enzymes were not essential for telomere recombination. Though mutations in the base-excision repair nucleases (Apn1 and Apn2) and AP lyases (Ntg1 and Ntg2) also did not affect telomere recombination ( Supplementary Figure S1a, k ), the apn1 apn2 double mutant caused a modest delay in type II survivor formation ( Supplementary Figure S1a ), suggesting that Apn1 and Apn2 might function redundantly to modulate telomere recombination.…”
Section: Resultsmentioning
confidence: 99%
“…We also analyzed three additional nucleotide excision repair genes, RAD10 , RAD14 and RAD17 , and found that none of them greatly affects type II telomere recombination ( Supplementary Figure S1p–r ). Thus, although mammalian nucleotide excision repair nucleases XPF and XPG have been reported to be involved in processing R-loop structures ( 16 , 17 , 36 ), the yeast nucleotide excision repair enzymes were not essential for telomere recombination. Though mutations in the base-excision repair nucleases (Apn1 and Apn2) and AP lyases (Ntg1 and Ntg2) also did not affect telomere recombination ( Supplementary Figure S1a, k ), the apn1 apn2 double mutant caused a modest delay in type II survivor formation ( Supplementary Figure S1a ), suggesting that Apn1 and Apn2 might function redundantly to modulate telomere recombination.…”
Section: Resultsmentioning
confidence: 99%
“…Mice overexpressing TRF2 show hypersensitivity to ultraviolet radiation compared to normal mice, resulting in telomere loss in their chromosomes. Conversely, expression of ERCC1-ERCC4 in TRF2-deficient cells leads to increased chromosomal end fusion ( 67 ). Mechanistically, ERCC1-ERCC4 can cleave at the 3’ end of telomeres, causing telomere shortening and premature aging in mice.…”
Section: The Ercc4 Gene and Its Biological Functionsmentioning
confidence: 99%
“…Similar to CFS-MiDAS, telomeric MiDAS requires SLX4 and RAD52 although MUS81 is not essential [ 123 ]. Furthermore, the CFS-MiDAS component XPF encourages ALT activity through break-induced synthesis given its activation of DDR pathways that result from the formation of telomeric R-loops [ 167 ]. Targeting SLX4, RAD52, and XPF could thus limit ALT activity through reducing telomeric MiDAS activity.…”
Section: Main Bodymentioning
confidence: 99%
“…Similarly, the PKMYT1 phosphorylates the Tyr15 and Thr14 positions of the CDK1/Cyclin B1 complex [ 171 ]. Targeting the WEE1 protein with inhibitors such as MK-1775 and the PKMYT1 protein with inhibitors such as RP-6306 is particularly promising given the heightened sensitivity of cells with ATRX-deficiencies to WEE1 inhibitors [ 167 , 172 ].…”
Section: Main Bodymentioning
confidence: 99%